2014
DOI: 10.4174/astr.2014.87.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Balanced approach can help initial outcomes: analysis of initial 50 cases of a new liver transplantation program in East Asia

Abstract: PurposeTo evaluate patient triage pattern and outcomes according to types of liver transplantation as part of a new liver transplant program developed in an East Asian country with a limited number of deceased donors.MethodsMedical records of initial 50 liver transplantations were reviewed retrospectively.ResultsTwenty-nine patients underwent deceased donor liver transplantation (DDLT) and 21 patients underwent living donor liver transplantation (LDLT). Mean model for end-stage liver disease scores of recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many studies have shown excellent LDLT outcomes in countries that have low DDLT rates. [2,11] For these reasons, a successful DDLT program does not always result in successful LDLT procedures. On the other hand, a high-volume hepatobiliary center with extensive experience in complex liver resection may have the opportunity to successfully develop LDLT programs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown excellent LDLT outcomes in countries that have low DDLT rates. [2,11] For these reasons, a successful DDLT program does not always result in successful LDLT procedures. On the other hand, a high-volume hepatobiliary center with extensive experience in complex liver resection may have the opportunity to successfully develop LDLT programs.…”
Section: Introductionmentioning
confidence: 99%